Enhancing nitrogen dynamics, soil health and yield intensification in rice-based cropping systems through rice straw incorporation - Majumder, Sitabhra; Shankar, Tanmoy; Saha, Niharendu; Sarkar , Supradip; Reddy, M Devender (Plant Science Today, 2025)
Use of a combine harvester for rice is responsible for leaving huge amounts of rice straw in harvested fields. As mechanisation in agriculture becomes widely adopted across the country, this leaves behind a good amount of straw. Farmers often burn this valuable organic resource, which increases greenhouse gas concentrations in the atmosphere. However, if this straw material is incorporated into the soil, it can significantly improve soil health, particularly its nutrient status. The beneficial effects of this practice are reflected in the higher yields of crops. Accordingly, this review focuses on nitrogen dynamics, crop performance, including yield and soil health status under rice ecosystems. Nitrogen (N) dynamics in soil-plant systems involve physical, chemical and biological processes. Physically, straw incorporation enhances soil structure, water retention and aggregation, providing a conducive environment for nutrient cycling. Chemically, it influences N immobilisation and mineralisation processes, balancing the availability of nitrogen for crops. Biologically, straw incorporation promotes microbial activity and diversity, particularly nitrogen-fixing and nitrifying bacteria, which play a crucial role in N availability to crops. These processes collectively improve soil nitrogen pools, enhance nitrogen use efficiency and reduce nitrogen losses through leaching or gaseous emissions. This results in synchronisation of nitrogen supply with crop demand, which will increase productivity and reduce pollution from the rice ecosystem.